2020
DOI: 10.1051/0004-6361/201936991
|View full text |Cite
|
Sign up to set email alerts
|

Type Ia supernovae from non-accreting progenitors

Abstract: Type Ia supernovae (SNe Ia) are manifestations of stars deficient of hydrogen and helium disrupting in a thermonuclear runaway. While explosions of carbon-oxygen white dwarfs are thought to account for the majority of events, part of the observed diversity may be due to varied progenitor channels. We demonstrate that helium stars with masses between ∼1.8 and 2.5 M may evolve into highly degenerate, near-Chandrasekhar mass cores with helium-free envelopes that subsequently ignite carbon and oxygen explosively a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…However, for the metallicity and mass range considered here, the assumption that the ensuing strong stellar wind blows off any remaining hydrogen within a short time remains a good approximation (Laplace et al 2020). Notably, we did not consider the lowest mass helium stars that could still produce SNe despite their low mass, and that may (Yoon et al 2010) or may not (Antoniadis et al 2020) retain their hydrogen. Whereas for the lower mass He stars considered here, a single star origin appears unlikely, it cannot be excluded that single stars with initial masses near 30 M may lose their envelope quickly after core hydrogen exhaustion (Smith & Owocki 2006;Petrov et al 2016).…”
Section: Modelmentioning
confidence: 99%
“…However, for the metallicity and mass range considered here, the assumption that the ensuing strong stellar wind blows off any remaining hydrogen within a short time remains a good approximation (Laplace et al 2020). Notably, we did not consider the lowest mass helium stars that could still produce SNe despite their low mass, and that may (Yoon et al 2010) or may not (Antoniadis et al 2020) retain their hydrogen. Whereas for the lower mass He stars considered here, a single star origin appears unlikely, it cannot be excluded that single stars with initial masses near 30 M may lose their envelope quickly after core hydrogen exhaustion (Smith & Owocki 2006;Petrov et al 2016).…”
Section: Modelmentioning
confidence: 99%
“…As a final remark we note that fallback SNe leading to the formation of NSs or LMG objects in symmetric explosions, may also carry broader implications for compact-object populations. For instance, they might contribute to the observed pulsar population in globular clusters, thereby serving as a substitute for L6, page 5 of 10 A&A 657, L6 (2022) NSs that formed via electron-capture SNe, which may be rarer than previously thought (Antoniadis et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…to be O(200 Myr), although it might be possible to form similar ONe cores via WD mergers (Schwab et al 2016). Antoniadis et al (2020), argued that the frequency of ONe SNe Ia can be comparable to the observed SN Ib/c rates. Considering the results presented here, we update the relative ratio between ONe SNe Ia and SNe Ib/c to be 0.17-0.30 at Z = 0.02 and 0.03-0.13 at Z = 10 −4 (assuming a Chabrier 2005, initial mass function).…”
Section: Shell Burning and Envelope Ejection Prior To Collapse Near-mentioning
confidence: 99%
“…For our models that feature residual carbon in their cores, the close succession of those two reactions-forced by the forbidden transition-could have a non-negligible effect on the overall outcome by reducing the carbon ignition density. Antoniadis et al (2020) presented a case study of two heliumstar models that develop a degenerate (C)ONe core and subsequently experience a thermal runaway when their central density is 9.2 log 10 (ρ c /g cm −3 ) 9.8. These stars likely avoid e-captures on 20 Ne, and produce a (C)ONe SN Ia.…”
Section: Other Sources Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation